PENGHINDARAN RISIKO KREDIT INVESTASI OLEH DEBITUR DI INDONESIA PASCA KRISIS 1997 - Aloysius Deno Hervino (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
This research aimed to estimate the short run and long run (steady state) model on credit market, which influenced on risk hindering behavior by debtor, and taking banking regulation into model as a shock. Analyzing on investment credit market is related with asymmetric information problem and dynamic decision. This research was using Autoregressive Distributed Lag Error Correction Model (ARDL-ECM) to analyze this behavior because all variables were integrated on different level. In the short run, the debtor behaviors is only influenced by real interest rate on rupiah working capital, and in the long run his behavior influenced by real interest rate on rupiah working capital, and expected on real national income. But debtor behavior do not influence by real interest rate on rupiah investment credit in short and long run. Banking regulation do not influence the investment credit risk hindering behavior on debtor. On average, every change in explanatory variables need 24 days by debtor to adjust his behavior on investment credit market.